(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Water is the most important basic need for all aspects of humanand ecosystem survival. This study aims to show the preferred method ofirrigation among the farmers at Jarif–Sirte site, Libya. It was carried outover a three week period, between 17th June and 9th July 2010.Themethods of irrigation were divided into modern methods (sprinkler anddrip systems) and traditional (surface systems-basin and furrow). Waterproductivity (WP) and profitability were the most important points thatwere covered. Two main methods for gathering data were used; the firstone was a questionnaire and the second was a focus group, also known asgroup discussion. The results indicated that adopting modern irrigationsystems, especially drip irrigation, can improve WP and profitabilitydramatically, whereas, water use can be reduced by at least one third withsimilar productivity for the other systems. Several factors which influenceadoption of advanced technologies have been noted in this study.Whereas the educated farmers tend to adopting modern irrigation methodsinstead of traditional methods. Moreover, economic factors are the mainbarrier to adoption as well as the fact that there will be no obligation topay the high cost of the electricity and water bills associated with thetraditional methods. The study recommend that famers should switch tomodern systems. Future studies should be carried out on the site forfurther information